IMPACT OF STRATEGIC MARKETING ON ENTERPRISE COMPETITIVENESS (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses strategic marketing. Also, the competitiveness of the enterprise is a guarantee of obtaining high economic indicators in modern market conditions. The competitiveness of an enterprise is a multifaceted concept, and includes not only the quality and price parameters of industrial products, but today it depends on the level of management, the existing management system of financial flows, innovation and investment components of its activities. In addition, competitiveness is influenced by the market conditions that are developing in a particular market, the level of competition affecting the enterprise from other market participants, technical equipment, and the level of use of innovations.